176PDCLK1 promotes tumour invasion and metastasis through epithelial-mesenchymal transition and the MEK/ERK pathway in esophageal squamous cell carcinoma. (24th November 2019) - Yao, J; Fan, X; Ge, Y; Liu, J; Weygant, N; An, G
Abstract: Background: Doublecortin-like kinase1 (DCLK1), a recently discovered cancer stem cell (CSC) marker in the colon and pancreatic cancer, contributes greatly to the malignancy of gastrointestinal cancers. Also, higher DCLK1 expression is reported in esophageal adenocarcinoma (EAC) compared to Barrett esophagus and normal tissue. However, studies on the effect of DCLK1 in esophageal squamous cell carcinoma (ESCC), which accounts for about 90% of diagnosed EC in Asia areas, were not yet reported. Methods: CRISPR/Cas9 genome-editing technique was used to knockout DCLK1 in ESCC cells (Kyse450, Kyse70). Subsequently, the proliferative and invasive potential of these cells was evaluated using Real-Time Cell Analyzer for proliferation, wound healing assay for migration, and transwell assay for invasion. Epithelial-mesenchymal transformation (EMT) associated transcriptional factors and MEK/ERK pathway were tested by western blot. In addition, the correlation heatmap between DCLK1 expression and EMT associated transcriptional factors, and MEK/ERK pathway was analyzed in R among 95 ESCC patients from The Cancer Genome Atla (TCGA) database. Results: CRISPR/Cas9 technology efficiently disrupted the DCLK1 gene and abrogated its expression in ESCC cell lines. DCLK1 deficiency significantly inhibited proliferation, migration and invasion of ESCC cells. DCLK1 deletion resulted in notable molecular changes including downregulation of mesenchymal markers such as Vimentin, ZEB1, Slug and Snail, and up-regulation of epithelial marker E-cadherin. Additionally, the phosphorylation of MEK/ERK pathway was inhibited in DCLK1-KO ESCC cells. Accordingly, evidence from TCGA ESCA demonstrated that human ESCCs expressing high levels of DCLK1 correlate with activated MEK/ERK pathway signaling suggesting greater EMT transition activity. Conclusions: CRISPR/Cas9-mediated knockout of DCLK1 results in a dramatic suppression of ESCC aggressiveness via inhibiting EMT and MEK/ERK pathway. Importantly, this study demonstrates DCLK1's functional significance in ESCC for the first time and provides a theoretical basis for the development of DCLK1-based biomarkers and targeted therapies. Legal entity responsible for the study: Jiannan Yao. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.